Comparative analysis of hydrogen sensing based on treated‑TiO2 in thick film gas sensor - Mohd Chachuli, Siti Amaniah; Hamidon, Mohd Nizar; Ertugrul, Mehmet; Coban, Omer; Mamat, Md. Shuhazlly; Shamsudin, Nur Hazahsha (Springer Nature, 2022)
This paper compares two TiO2 thick flm gas sensors to the hydrogen at elevated operating temperatures. The frst gas sensor was prepared by applying nitrogen treatment at 200 °C for 2 h to the TiO2 powder before the TiO2 paste was prepared. The second gas sensor was prepared using TiO2 powder without purifcation to make the TiO2 paste. Both TiO2 pastes were prepared by mixing the sensing material with an organic binder. Both pastes were deposited on an alumina substrate using a screen-printing technique and annealed at 500 °C for 30 min under ambient air. FESEM and XRD characterizations were carried out to investigate the morphology and elemental composition. The results revealed that the TiO2 thick flm with nitrogen treatment produced slightly higher crystallinity and smaller crystallite sizes for the anatase and rutile phases than the TiO2 thick flm without nitrogen treatment. In terms of resistivity, the WTN gas sensor produced lower resistivity than the WON gas sensor for operating temperatures below 200 °C. The results were found that the WON gas sensor had higher sensitivity than the WTN gas sensor to various concentrations of hydrogen at the operating temperature of 150 °C, 200 °C, and 250 °C. Both gas sensors also produced similar optimum operating temperatures, which occurred at 200 °C. The sensitivity of the WON gas sensor was approximately 6.30, 8.39, 12.70, 15.92, and 19.87 optimum operating temperatures to 100 ppm, 300 ppm, 500 ppm, 700 ppm, and 1000 ppm of hydrogen, respectively. In addition, the WTN gas sensor has better stability characteristics for higher operating temperatures.